(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Mungbean is an important pulse crop in Bangladesh for nutrition, the economy, and food security, as well as a source of protein for the majority of the people. The study was carried out to better understand farmers’ views toward mungbean production, the factors affecting mungbean adoption, and the financial profitability of mungbean cultivation. A structured and pre-tested interview schedule was used to interview 90 mungbean farmers that were randomly selected from different villages in Patuakhali Sadar Upazila, Patuakhali district for collecting field level data. A combination of descriptive, mathematical and statistical techniques was used to analyze the data. Profitability analysis showed that mungbean production was profitable because the net return of its cultivation was Tk. 21,959/ha and BCR was more than unity (1.73). The study revealed that short duration crop, sharing work within household members, crop diversification, minimum tillage, employment creation, and income generation significantly influenced farmers to cultivate mungbean than any other crop. Problem facing index pointed out high price of seed and fertilizer, lack of good quality seed and fertilizer, inadequate extension service as a production related problem and lack of value added product development and transport facility, low market price of output and lack of storage facilities were identified as a major marketing problem of mungbean cultivation. Bangladesh J. Agril. Res. 46(4): 385-396, December 2021